Pengaruh variasi konsentrasi tempe kedelai dan kulit pisang ambon (Musa paradisiaca) terhadap aktivitas antioksidan dan daya terima steak tempe - Rofrofiyyah Ula; Septy Handayani (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Tempe contains bioactive compounds in the form of isoflavones, scientifically proven to have antioxidant abilities. In addition, banana peel antioxidants are quite high compared to the fruit flesh. Food products that are high in antioxidants have the potential to reduce various degenerative diseases. The combination of antioxidants from soybean tempeh and Ambon banana peel is expected to be one of the efforts to maintain health by minimizing the risk factors for chronic disease due to hypercholesterolemia.Objective: The study aimed to analyze the effect of varying soy tempeh and Ambon banana peel concentrations on tempeh steak's antioxidant activity and acceptability.Method: Research using design Quasi-Experiment, with one group posttest-only design. This research was conducted in January-March 2023. The research procedure began with making tempeh steak with the formulation of the comparison of soybean tempe: Ambon banana skin, namely F1 (30%: 70%), F2 (40%: 60%), F3 (50%: 50%), F4 (60%:40%). There were 4 experimental groups and 3 repetitions. Then, the antioxidant test was carried out using the DPPH method at the Jember State Polytechnic Bioscience Laboratory. The data was analyzed using this method by Kruskal Wallis. Acceptance test was carried out on 30 untrained panelists using the hedonic method at the Integrated Laboratory of FKM University of Jember and data analysis using the test Friedman, at a significance level of 95% CI.Results: The results of the antioxidant activity test showed no significant difference in the average antioxidant activity of tempeh steak (p= 0,951). The average results of antioxidant activity were F1 (70,61%), F2 (71.77%,) F3 (70,64%), F4 (71,44%). Acceptability test results showed significant differences in terms of aroma (p= 0,004), taste (p= 0,026), and overall (p= 0,004), but not significantly different in terms of color (p= 0,055) and texture (p= 0,157). The most preferred experimental group is F4[A2] (p= 0,004).Conclusion: The content of soy tempeh and Ambon banana skin contribute to each other in increasing the percentage of antioxidant inhibition so that it affects the increase in the antioxidant activity of tempeh steak. The higher the concentration of soy tempeh used, the higher the level of preference for the acceptance of tempeh steak. The product recommended in this study was the F4 sample with an average antioxidant activity yield of 71,44%, and the panelists preferred the F4 sample.